2006
DOI: 10.1007/s00348-006-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

Mass flow rate measurements in gas micro flows

Abstract: International audienceThe main objective of this experimental investigation on the gas flow slip regime is to measure the mass flow rate in isothermal steady flows through cylindrical micro tubes. Two technical procedures devoted to mass flow rate measurements are compared, and the measured values are also compared with the results yielded by different approximated analytical solutions of the gas dynamics continuum equations. Satisfactory results are obtained and the way is clearly opened to measuring mass flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 20 publications
8
105
1
Order By: Relevance
“…The standard deviation of coefficient a is calculated following the method proposed in (Ewart et al 2006) and is found to be less than 0.5%. Therefore, the overall uncertainty of the mass flow rate measurement is calculated from…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The standard deviation of coefficient a is calculated following the method proposed in (Ewart et al 2006) and is found to be less than 0.5%. Therefore, the overall uncertainty of the mass flow rate measurement is calculated from…”
Section: Methodsmentioning
confidence: 99%
“…• Several authors have developed a method based on the tracking of a liquid droplet (Pong et al 1994;Harley et al 1995;Lalonde 2001;Zohar et al 2002;Maurer et al 2003;Colin et al 2004;Ewart et al 2006). In this method, the droplet is pushed by the gas flow, and its tracking allows a direct measurement of the volume flow rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DT technique is commonly used for measurement of microflows emerging from microchannels (Harley et al, 1995;Zohar et al, 2002;Maurer et al 2003;Colin et al, 2004;Ewart et al, 2006;Pitakarnnop et al, 2010). When the downstream of a capillary is open to atmosphere, the flow measurement can be performed using a soap flowmeter (Celata et al, 2007).…”
Section: Droplet Tracking Techniquementioning
confidence: 99%
“…Studies involving flows in transition and near free molecular regimes require very low downstream pressures. For example, Pitakarnnop et al (2010) and Ewart et al (2006) reported flow measurements at downstream pressures of as low as 1,928 Pa and 1,101 Pa, respectively. At such low pressures, a soap bubble and even a soap liquid droplet would quickly evaporate making measurement impossible.…”
Section: Droplet Tracking Techniquementioning
confidence: 99%